The impact of strategic knowledge management processes on social innovation practises - Muhamad Nizam, Jali (2017)
Only recently, various developed countries had been chanting out social innovation as the new paradigm of innovation outcome strategy in addressing social, economic and technological issues in a concurrent way. Social innovation in the context of strategic knowledge management processes creates superior knowledge resource which regard as a new and novel solution that can be embedded into product, process and service which in turn leads to the outcome of improving the quality of people’s life, stimulate economic growth and enhance technological aspect. However, social innovation is very much connected with pure social aspects. This study examine and explore the impact of strategic knowledge management processes on social innovation within the context of Malaysian university-industry-community partnership projects funded by the Knowledge Transfer Partnership (KTP) grant program. The main data for this study was collected through survey questionnaires via personnel administered and internet email from 218 project leaders of Malaysian university-industry-community partnership projects. The data for this study were also obtained through face-to-face interview sessions with the academic, industry and community actors within the partnership projects. These data were collected from the period of May 2016 till October 2016. The data was analysed by using Statistical Package for Social Science (SPSS) version 19 software and the content of the interviews data was validated by experience and expert qualitative researchers within the respective field. The findings of this study indicate a significant positive relationship between strategic knowledge management processes and social innovation. Further, hyphotheses testing results also demonstrated that socialization towards leveraging new knowledge resource, ability to transform and absorb new knowledge resource, ICT skills and knowledge and selection process of actors is somewhat needs serious improvements. Furthermore, syncronization of missions, objectives and priorities, high bureaucracy practices, business disclosures issues, innovation specification requirements issues, understanding and commitment issues and financial constraints issues must be dealt with accordingly so that can provide improvements and added value to the existing policy and procedures.